2020
DOI: 10.1101/2020.06.22.152066
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amyloid-beta mediates homeostatic synaptic plasticity

Abstract: The physiological role of the amyloid-precursor protein (APP) is insufficiently understood. 29 Recent work has implicated APP in the regulation of synaptic plasticity. Substantial evidence 30 exists for a role of APP and its secreted ectodomain APPsα in Hebbian plasticity. Here, we 31 addressed the relevance of APP in homeostatic synaptic plasticity using organotypic tissue 32 cultures of APP -/mice. In the absence of APP, dentate granule cells failed to strengthen their 33 excitatory synapses homeostatical… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 80 publications
1
7
0
Order By: Relevance
“…Interestingly, we observed that the mean firing rates were similar between TTX, vehicle and bicuculline treated WT neurons after 48 h consistent with findings suggesting that while single unit firing is unstable, networks maintain surprisingly stable firing frequencies (Slomowitz et al, 2015). Aβ and APP have been implicated in normal HSP (Gilbert et al, 2016;Galanis et al, 2021), and APP/PS1 mice were recently shown to have defective downscaling during sleep (Zarhin et al, 2022). Defective HSP could help explain why AD transgenic mice are more susceptible to pharmacologically-induced and spontaneous seizures (Minkeviciene et al, 2009;Reyes-Marin and Nuñez, 2017) and could provide a framework for explaining the increased sensitivity to seizures in AD patients (Pandis and Scarmeas, 2012).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, we observed that the mean firing rates were similar between TTX, vehicle and bicuculline treated WT neurons after 48 h consistent with findings suggesting that while single unit firing is unstable, networks maintain surprisingly stable firing frequencies (Slomowitz et al, 2015). Aβ and APP have been implicated in normal HSP (Gilbert et al, 2016;Galanis et al, 2021), and APP/PS1 mice were recently shown to have defective downscaling during sleep (Zarhin et al, 2022). Defective HSP could help explain why AD transgenic mice are more susceptible to pharmacologically-induced and spontaneous seizures (Minkeviciene et al, 2009;Reyes-Marin and Nuñez, 2017) and could provide a framework for explaining the increased sensitivity to seizures in AD patients (Pandis and Scarmeas, 2012).…”
Section: Discussionsupporting
confidence: 85%
“…Structural homeostatic synaptic plasticity is known to occur at three main locations: (1) at the post-synapse involving reduced or increased levels of surface receptors (Turrigiano et al, 1998) ; (2) at the axon initial segment (AIS) by either increasing or decreasing its length or by shifting the AIS further out into the axon (Wefelmeyer et al, 2016); or (3) at the pre-synapse by modifying how much neurotransmitter is stored in synaptic vesicles or through homeostatic maintenance of presynaptic exocytosis (Delvendahl et al, 2019). Of note, Aβ was suggested to overshoot normal homeostatic scaling in response to sensory deprivation in vivo or TTX-mediated inhibition in vitro (Gilbert et al, 2016), and Aβ was recently shown to regulate homeostatic synaptic upscaling after activity blockade in dentate gyrus in vivo (Galanis et al, 2021). Our findings that APP/PS1 neurons do not increase their activity after 48 h of TTX treatment nor decrease firing rate after 48 h of bicuculline treatment suggest that Aβ/APP play important roles not only in adjusting to activity blockade but also have roles in homeostatic downscaling in response to excessive activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nehls commented that the effect of Aβ on memory is dose dependent with higher concentrations "preserving new memory traces from being overridden by subsequent events that are to be memorized", though the basis of this statement was not elaborated (Nehls, 2016). Many studies implicate Aβ in metaplastic events (Galanis et al, 2020;Gilbert et al, 2016;Jang and Chung, 2016;Li et al, 2017a;Megill et al, 2015;Peineau et al, 2018) and Puzzo's group suggest that by inducing conversion of early LTP to late LTP, oAβ42 plays a part in synaptic tagging (Gulisano et al, 2019). Parihar and Brewer emphasize the modulatory effects of Aβ on neuroplasticity, noting that aging and Aβ independently decrease neuronal plasticity, also pointing out that Aβ-induced neurotoxicity is age-dependent and that the longevity of humans may contribute to AD by rendering the brain vulnerable to Aβ-induced neurotoxicity (Parihar and Brewer, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…To many, these findings substantiate the view that Aβ42 acts largely with sinister intentions. However, there is increasing recognition that Aβ42 and other APP-derivatives play important beneficial roles in modulating synaptic plasticity (Li et al, 2017b;Morley et al, 2019;Parihar and Brewer, 2010;Puzzo et al, 2012;Ricciarelli and Fedele, 2018;Venkitaramani et al, 2007) including metaplastic events such as STC and synaptic scaling (Galanis et al, 2020;Gilbert et al, 2016;Jang and Chung, 2016;Li et al, 2017a;Megill et al, 2015;Peineau et al, 2018). This is not to say that Aβ42 is always harmless (see section 21), indeed there is little doubt Aβ42 can be very toxic at certain concentrations and in certain forms.…”
Section: Aβ and Neuroplasticitymentioning
confidence: 99%